2022
DOI: 10.3390/ijerph19169993
|View full text |Cite
|
Sign up to set email alerts
|

Key Influencing Factors and Optimization Strategy of Epidemic Resilience in Urban Communities—A Case Study of Nanjing, China

Abstract: COVID-19 has posed a significantly severe impact on both people’s lives and the global economic development. Increasing the community epidemic resilience will considerably improve the national public health emergency response capacity from bottom to top. This study identifies the influencing factors of community epidemic resilience through systematic literature review under the 4R framework, then obtains the relationships of influencing factors through Interpretive structural model, and finally assesses the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 80 publications
(89 reference statements)
0
5
0
Order By: Relevance
“…The CEPCC is closely intertwined with their resilience in the face of crises. Resilient communities have demonstrated stronger resistance and recover quicker than traditional communities amidst the impact of epidemics (14). Since the outbreak of COVID-19, numerous scholars have researched the factors that impact the CEPCC.…”
Section: Literature Review and Research Framework Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The CEPCC is closely intertwined with their resilience in the face of crises. Resilient communities have demonstrated stronger resistance and recover quicker than traditional communities amidst the impact of epidemics (14). Since the outbreak of COVID-19, numerous scholars have researched the factors that impact the CEPCC.…”
Section: Literature Review and Research Framework Literature Reviewmentioning
confidence: 99%
“…Galbusera et al identified infrastructure as a critical factor that influences the ability of urban communities to combat epidemics, including elements such as basic necessities, protective equipment, public health resources, and emotional resources (15). Furthermore, Cui et al conducted comprehensive research on the CEPCC and concluded that economic level, social networks, emergency response and daily management, medical resources and public services, as well as experiences in disasters and information technology, are key factors that influence this capacity, in addition to the availability of hardware and software resources such as infrastructure and management capacity (14). On the other hand, some scholars have highlighted the role of the government in influencing the CEPCC.…”
Section: Literature Review and Research Framework Literature Reviewmentioning
confidence: 99%
“…Cui et al, argue that a resilient city must demonstrate four characteristics: robustness, redundancy, rapidity, and resourcefulness [13]. A multi-perspective resilience approach based on the 4R framework provides a holistic view of a city's resilience performance in response to public health disasters.…”
Section: The Definition and Characteristics Of Resiliencementioning
confidence: 99%
“…After consulting and organizing existing policies and research, this paper identifies eight resilience assessment indicators, including economic level, social network, emergency response, daily management, medical resources, public service resources, experience in disaster, and information technology, which are illustrated in Figure 2 [13,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Economic level and social network are regarded as constituting robustness.…”
Section: The Identification Of Resilience Assessment Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation